A stone repair and renewal agent

By using a stone repair and renewal agent containing nano-scale materials and carbon-based nanoparticles, the problems of difficult and cost of stone repair in the prior art are solved, and efficient and stable stone repair and renewal effects are achieved.

CN116477909BActive Publication Date: 2025-02-11XIAMEN SINO CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310286152.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-23
Publication Date
2025-02-11
Estimated Expiration
2043-03-23

AI Technical Summary

Technical Problem

Existing stone repair technology is difficult to effectively reduce the difficulty and cost of stone surface repair, and conventional grinding methods may damage the crystalline layer on the stone surface, affecting the repair effect.

Method used

Using a stone repair and renewal agent, which includes sulfaluminate cement, nano-silicon carbide powder, nano-scale silicone oil, carbon-based nanoparticles, penetrants and water solvents, the dispersion of the repair agent is enhanced through the combination of these nano-scale materials. Stability and improve binding capacity through the core-shell structure of carbon-based nanoparticles.

Benefits of technology

It significantly reduces the difficulty and cost of stone surface repair. By stably dispersing it on the stone surface and forming it in pores, it achieves efficient repair and renewal, and improves the surface chemical stability and structural strength of the stone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116477909B_ABST
    Figure CN116477909B_ABST
Patent Text Reader

Abstract

The present application discloses a stone repair and renewal agent, which relates to the field of stone repair technology, and includes the following components by weight: 15-25 parts of sulphoaluminate cement; 8-11 parts of nano silicon carbide powder; 7-12 parts of nano silicone oil; 2-4 parts of carbon-based nanoparticles; 0.4-1.8 parts of penetrant; 8-12 parts of water solvent; wherein the carbon-based nanoparticles are composed of a carbon-based core and a shell coated on the carbon-based core. The present application has the effect of significantly reducing the difficulty and cost of stone surface repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of stone repair, and in particular to a stone repair and renewal agent. Background Art

[0002] Quartz is an artificial stone slab, but because of its irregular arrangement and rich and varied colors, it has an appearance comparable to natural stone and is widely used in furniture decoration. Not only does it look good, but because it is an artificial stone, it can be artificially synthesized during the production process, so it has advantages that natural stone does not have, such as antibacterial, wear-resistant, high temperature resistant, non-toxic, and radiation-free.

[0003] As one of the important components of stone, although quartz stone is artificially synthesized and many new materials are added during synthesis to avoid damage caused by wear, high temperature, positive acid and alkali, it still has problems such as whitening of the surface that affect the appearance of use. Natural marble is also easily contaminated by alkaline or acidic cleaning agents. For example, cleaning products such as hand sanitizer, soap, toilet cleaner, etc., after dripping on the surface of stone, cause the surface of stone to slowly corrode, resulting in the phenomenon of whitening and even loss of gloss on the surface of stone.

[0004] In the prior art, grinding and crystallization are usually used for treatment. However, the grinding tools are highly professional, and the crystal layer on the stone surface may be destroyed during the grinding process, which directly affects the feasibility of surface repair of the stone countertop. The corresponding grinding cost is high, which in turn affects people's enthusiasm for stone surface repair, and needs to be improved. Summary of the invention

[0005] In view of this, the purpose of this application is to provide a stone repair and renewal agent to achieve the purpose of significantly reducing the difficulty and cost of stone surface repair. The specific scheme is as follows:

[0006] A stone repair and renewal agent, comprising the following components in parts by weight:

[0007] Sulphoaluminate cement 15-25 parts;

[0008] 8-11 parts of nano silicon carbide powder;

[0009] 7-12 parts of nano silicone oil;

[0010] 2-4 parts of carbon-based nanoparticles;

[0011] Penetrant 0.4-1.8 parts;

[0012] 8-12 parts of water solvent;

[0013] The carbon-based nanoparticles are composed of a carbon-based core and a shell covering the carbon-based core.

[0014] Preferably, the particle size of the nano silicon carbide powder is 30-100 nm.

[0015] Preferably: the preparation method of the carbon-based nanoparticles includes s1, introducing the carbon-based material into a grinding jar for grinding to obtain a nano-scale carbon-based material; s2, adding aluminum dihydrogen phosphate in a weight ratio of 1:0.2-0.6 to the nano-scale carbon-based material into the grinding jar, and stirring and mixing to obtain a carbon-based material with aluminum dihydrogen phosphate adhered to the surface; s3, adding silicon dioxide in a weight ratio of 1:0.05-0.12 to the carbon-based material with aluminum dihydrogen phosphate adhered to the surface, and continuing to stir to obtain a mixed slurry; s4, introducing the mixed slurry into a vacuum drying oven for drying to obtain a carbon-based core coating material; s5, grinding, ultrasonically dispersing and stirring, drying and sintering the carbon-based core coating material to obtain carbon-based nanoparticles.

[0016] Preferably: in s1, the grinding medium of the grinding jar is ethanol or water, and the grinding speed is 1200-1800 r / min, the time is 4-24 h, and the particle size of the nano-scale carbon-based material is 80-300 nm.

[0017] Preferably: in s3, the stirring time is continued for 2-18 hours.

[0018] Preferably, in s3, the step further includes adding lithium sulfate to the nano-scale carbon-based material in a weight ratio of 1:0.08-0.24 into the carbon-based material with aluminum dihydrogen phosphate adhered to the surface.

[0019] Preferably: in s4, the drying temperature of the vacuum drying oven is 120-280°C, and the drying time is 4-32h.

[0020] Preferably: in s5, the grinding is carried out in a grinding jar and anhydrous ethanol is used as the solvent, the ultrasonic dispersion and stirring are controlled for 1-12 hours, the drying is controlled at 100-300°C, and the control time is 2-24 hours, the sintering is controlled at 200-400°C, and the control time is 4-24 hours.

[0021] Preferably: the carbon-based core is graphene, graphene oxide and / or silicon carbide fiber; the shell is composed of aluminum dihydrogen phosphate and silicon dioxide or aluminum dihydrogen phosphate, silicon dioxide and lithium sulfate.

[0022] Preferably, the penetrant is diisooctyl maleate sulfonate.

[0023] It can be seen from the above scheme that the present application provides a stone repair and renewal agent, which has the following beneficial effects:

[0024] 1. Nano-scale materials such as nano-silicon carbide powder, nano-scale silicone oil and carbon-based nano-particles are used as the main components to improve the dispersion stability of the stone repair and renewal agent when combined with sulphoaluminate cement. When applied to stone repair and renewal, the stone repair and renewal agent is stably dispersed on the surface of the stone to be repaired and renewed, and through the defects such as pores formed on the surface of the stone, the stone can be repaired and renewed efficiently;

[0025] 2. Through the core-shell structure adopted by the carbon-based nanoparticles, the adsorption of the carbon-based core is enhanced in the synergy of aluminum dihydrogen phosphate and silicon dioxide or aluminum dihydrogen phosphate, silicon dioxide and lithium sulfate as the shell, so as to enhance the binding ability of the carbon-based nanoparticles with the penetrant, water solvent, nano-grade silicone oil, sulfoaluminate cement and nano silicon carbide powder, so that the stone repair and renewal agent is stably dispersed on the surface of the stone to be repaired and renewed, and through the defects such as pores formed on the surface of the stone, the stone can be repaired and renewed efficiently;

[0026] 3. During the preparation of carbon-based nanoparticles, aluminum dihydrogen phosphate, while acting as a binder, forms an amorphous structure due to the influence of temperature rise, and the amorphous structure has a crack and mosaic state, so that the amorphous structure is combined through bridging hydrogen bonds, so that the hydrogen bonds can maintain an effective combination state with the penetrant, water solvent, nano-grade silicone oil, sulphoaluminate cement and nano-silicon carbide powder, and thus the stone repair and renewal agent can achieve the purpose of significantly reducing the difficulty and cost of stone surface repair;

[0027] 4. Aluminum dihydrogen phosphate decomposes during the heating process to produce some aluminum metaphosphate, which in turn improves the surface chemical stability and structural strength of the stone to be repaired and renewed. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0029] Figure 1 This is a schematic diagram of the structure of the carbon-based nanoparticles disclosed in this application.

[0030] Explanation of the reference numerals: 1. carbon-based core; 2. shell. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0032] It should be mentioned that the stone repair and renewal agent of the present application will be described in detail as follows.

[0033] The method of using the stone repair and renewal agent of the present application is to first clean the surface of the stone to be repaired and renewed and keep it dry, then apply the stone repair and renewal agent to the surface of the stone to be repaired and renewed, let it stand and dry, and then repeat the application according to the glossiness until the glossiness reaches a uniform level.

[0034] like Figure 1 As shown, a stone repair and renewal agent includes 15-25 parts by weight of sulphoaluminate cement, 8-11 parts of nano silicon carbide powder, 7-12 parts of nano silicone oil, 2-4 parts of carbon-based nanoparticles, 0.4-1.8 parts of penetrant and 8-12 parts of water solvent. The carbon-based nanoparticles are composed of a carbon-based core and a shell covering the carbon-based core.

[0035] It should be noted that the particle size of the nano silicon carbide powder is 30-100nm. The preparation method of carbon-based nanoparticles includes s1, introducing the carbon-based material into a grinding jar for grinding and obtaining a nano-scale carbon-based material; s2, adding aluminum dihydrogen phosphate in a weight ratio of 1:0.2-0.6 to the nano-scale carbon-based material into the grinding jar, and stirring and mixing to obtain a carbon-based material with aluminum dihydrogen phosphate adhered to the surface; s3, adding silicon dioxide in a weight ratio of 1:0.05-0.12 to the carbon-based material with aluminum dihydrogen phosphate adhered to the surface, and continuing to stir to obtain a mixed slurry; s4, introducing the mixed slurry into a vacuum drying oven for drying, and obtaining a carbon-based core coating material; s5, grinding, ultrasonically dispersing and stirring, drying and sintering the carbon-based core coating material to obtain carbon-based nanoparticles.

[0036] in:

[0037] In s1, the grinding medium of the grinding jar is ethanol or water, and the grinding speed is 1200-1800 r / min, the time is 4-24 h, and the particle size of the nano-scale carbon-based material is 80-300 nm.

[0038] In s3, stirring is continued for 2-18 hours; and lithium sulfate is added to the carbon-based material with aluminum dihydrogen phosphate adhering to the surface thereof at a weight ratio of 1:0.08-0.24 to the nano-scale carbon-based material.

[0039] In s4, the drying temperature of the vacuum drying oven is 120-280°C, and the drying time is 4-32h.

[0040] In s5, grinding is carried out in a grinding jar and anhydrous ethanol is used as a solvent; the control time of ultrasonic dispersion and stirring is 1-12 hours; the control temperature of drying is 100-300°C, and the control time is 2-24 hours; the control temperature of sintering is 200-400°C, and the control time is 4-24 hours.

[0041] It should be noted that the carbon-based core is graphene, graphene oxide and / or silicon carbide fiber; the shell is composed of aluminum dihydrogen phosphate and silicon dioxide or aluminum dihydrogen phosphate, silicon dioxide and lithium sulfate. The penetrant is diisooctyl maleate sulfonate.

[0042] Embodiment 1

[0043] like Figure 1 As shown, a stone repair and renewal agent includes 15 parts by weight of sulphoaluminate cement, 8 parts of nano silicon carbide powder, 7 parts of nano silicone oil, 2 parts of carbon-based nanoparticles, 0.4 parts of penetrant and 8 parts of water solvent. The carbon-based nanoparticles are composed of a carbon-based core and a shell covering the carbon-based core.

[0044] It should be noted that the particle size of nano silicon carbide powder ranges from 30 to 100 nm. The preparation method of carbon-based nanoparticles includes s1, introducing carbon-based materials into a grinding jar for grinding and obtaining nano-scale carbon-based materials; s2, adding aluminum dihydrogen phosphate in a weight ratio of 1:0.2 to the grinding jar and stirring and mixing to obtain a carbon-based material with aluminum dihydrogen phosphate adhered to the surface; s3, adding silicon dioxide in a weight ratio of 1:0.05 to the carbon-based material with aluminum dihydrogen phosphate adhered to the surface, and continuing to stir to obtain a mixed slurry; s4, introducing the mixed slurry into a vacuum drying oven for drying and obtaining a carbon-based core coating material; s5, grinding, ultrasonically dispersing and stirring, drying and sintering the carbon-based core coating material to obtain carbon-based nanoparticles.

[0045] in:

[0046] In s1, the grinding medium of the grinding jar is ethanol or water, and the grinding speed is 1200 r / min, the time is 4 h, and the particle size of the nano-scale carbon-based material is 80 nm.

[0047] In s3, stirring is continued for 2 hours; and the process includes adding lithium sulfate in a weight ratio of 1:0.08 to the nano-scale carbon-based material into the carbon-based material with aluminum dihydrogen phosphate adhering to the surface.

[0048] In s4, the drying temperature of the vacuum drying oven is 120°C and the drying time is 4 h.

[0049] In s5, grinding is carried out in a grinding jar and anhydrous ethanol is used as a solvent; the control time of ultrasonic dispersion and stirring is 1 hour; the control temperature of drying is 100°C and the control time is 2 hours; the control temperature of sintering is 200°C and the control time is 4 hours.

[0050] It should be noted that the carbon-based core is graphene oxide, the shell is composed of aluminum dihydrogen phosphate and silicon dioxide, and the penetrant is diisooctyl maleate sulfonate.

[0051] Embodiment 2

[0052] like Figure 1 As shown, a stone repair and renewal agent includes 20 parts by weight of sulphoaluminate cement, 10 parts of nano silicon carbide powder, 10 parts of nano silicone oil, 3 parts of carbon-based nanoparticles, 0.8 parts of penetrant and 10 parts of water solvent. The carbon-based nanoparticles are composed of a carbon-based core and a shell covering the carbon-based core.

[0053] It should be noted that the particle size of nano silicon carbide powder ranges from 30 to 100 nm. The preparation method of carbon-based nanoparticles includes s1, introducing carbon-based materials into a grinding jar for grinding and obtaining nano-scale carbon-based materials; s2, adding aluminum dihydrogen phosphate in a weight ratio of 1:0.4 to the nano-scale carbon-based materials into the grinding jar, and stirring and mixing to obtain a carbon-based material with aluminum dihydrogen phosphate adhered to the surface; s3, adding silicon dioxide in a weight ratio of 1:0.09 to the nano-scale carbon-based materials into the carbon-based material with aluminum dihydrogen phosphate adhered to the surface, and continuing to stir to obtain a mixed slurry; s4, introducing the mixed slurry into a vacuum drying oven for drying, and obtaining a carbon-based core coating material; s5, grinding, ultrasonically dispersing and stirring, drying and sintering the carbon-based core coating material to obtain carbon-based nanoparticles.

[0054] in:

[0055] In s1, the grinding medium of the grinding jar is ethanol or water, and the grinding speed is 1500 r / min, the time is 16 h, and the particle size of the nano-scale carbon-based material is 80-300 nm.

[0056] In s3, stirring is continued for 10 hours; and the process includes adding lithium sulfate in a weight ratio of 1:0.15 to the nano-scale carbon-based material into the carbon-based material with aluminum dihydrogen phosphate adhering to the surface.

[0057] In s4, the drying temperature of the vacuum drying oven is 190°C and the drying time is 20 h.

[0058] In s5, grinding is carried out in a grinding jar and anhydrous ethanol is used as a solvent; the control time of ultrasonic dispersion and stirring is 6 hours; the control temperature of drying is 200°C and the control time is 12 hours; the control temperature of sintering is 300°C and the control time is 12 hours.

[0059] It should be noted that the carbon-based core is graphene and silicon carbide fiber in a mass ratio of 1:1; the shell is composed of aluminum dihydrogen phosphate, silicon dioxide and lithium sulfate. The penetrant is diisooctyl maleate sulfonate.

[0060] Embodiment 3

[0061] like Figure 1 As shown, a stone repair and renewal agent includes 25 parts by weight of sulphoaluminate cement, 11 parts of nano silicon carbide powder, 12 parts of nano silicone oil, 4 parts of carbon-based nanoparticles, 1.8 parts of penetrant and 12 parts of water solvent. The carbon-based nanoparticles are composed of a carbon-based core and a shell covering the carbon-based core.

[0062] It should be noted that the particle size of nano silicon carbide powder ranges from 30 to 100 nm. The preparation method of carbon-based nanoparticles includes s1, introducing carbon-based materials into a grinding jar for grinding and obtaining nano-scale carbon-based materials; s2, adding aluminum dihydrogen phosphate in a weight ratio of 1:0.6 to the nano-scale carbon-based materials into the grinding jar, and stirring and mixing to obtain a carbon-based material with aluminum dihydrogen phosphate adhered to the surface; s3, adding silicon dioxide in a weight ratio of 1:0.12 to the carbon-based material with aluminum dihydrogen phosphate adhered to the surface, and continuing to stir to obtain a mixed slurry; s4, introducing the mixed slurry into a vacuum drying oven for drying, and obtaining a carbon-based core coating material; s5, grinding, ultrasonically dispersing and stirring, drying and sintering the carbon-based core coating material to obtain carbon-based nanoparticles.

[0063] in:

[0064] In s1, the grinding medium of the grinding jar is ethanol or water, the grinding speed is 1800 r / min, the time is 24 h, and the particle size of the nano-scale carbon-based material is 300 nm.

[0065] In s3, stirring is continued for 18 hours; and the process includes adding lithium sulfate in a weight ratio of 1:0.24 to the nano-scale carbon-based material into the carbon-based material with aluminum dihydrogen phosphate adhering to the surface.

[0066] In s4, the drying temperature of the vacuum drying oven is 280°C and the drying time is 32 h.

[0067] In s5, grinding is carried out in a grinding jar and anhydrous ethanol is used as a solvent; the control time of ultrasonic dispersion and stirring is 12 hours; the control temperature of drying is 300°C and the control time is 24 hours; the control temperature of sintering is 400°C and the control time is 24 hours.

[0068] It should be noted that the carbon-based core is silicon carbide fiber, the shell is composed of aluminum dihydrogen phosphate, silicon dioxide and lithium sulfate, and the penetrant is diisooctyl maleate sulfonate.

[0069] Comparative Example 1

[0070] The difference between Comparative Example 1 and Example 1 is that the carbon-based nanoparticles in Comparative Example 1 consist only of carbon-based cores.

[0071] Comparative Example 2

[0072] The difference between Comparative Example 2 and Example 1 is that no penetrant is added in Comparative Example 2.

[0073] Comparative Example 3

[0074] The difference between Comparative Example 3 and Example 1 is that the penetrant in Comparative Example 3 is fatty alcohol polyoxyethylene ether.

[0075] The following items were tested on the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3:

[0076] 1. Glossiness test, tested in accordance with GB / T 13891-2008;

[0077] 2. Shore hardness test: test according to GB / T 99665-2001.

[0078] And obtain the following test data:

[0079] Test results table

[0080]

[0081] It can be seen from the test result table that the stone repaired and renewed by the stone repair and renewal agent of the present application has the effect of significantly improving the Shore hardness of the surface, and the glossiness of the stone surface after being coated with the stone repair and renewal agent of the present application will be significantly improved, thereby achieving the purpose of efficient repair and renewal of the stone, and having the effect of reducing the difficulty and cost of repair and renewal.

[0082] In summary, the present application provides a stone repair and renewal agent, which adopts nano-scale materials such as nano-silicon carbide powder, nano-scale silicone oil and carbon-based nanoparticles as main components to improve the dispersion stability of the stone repair and renewal agent when combined with sulfoaluminate cement, so that when applied to stone repair and renewal, the stone repair and renewal agent is stably dispersed on the surface of the stone to be repaired and renewed, and through the defects such as pores formed on the surface of the stone, efficient repair and renewal of the stone is achieved; at the same time, through the core-shell structure adopted by the carbon-based nanoparticles, the adsorption effect of the carbon-based core is enhanced in the synergy of aluminum dihydrogen phosphate and silicon dioxide or aluminum dihydrogen phosphate, silicon dioxide and lithium sulfate as the shell, so as to improve the binding ability of the carbon-based nanoparticles with the penetrant, water solvent, nano-scale silicone oil, sulfoaluminate cement and nano-silicon carbide powder, so that the stone repair and renewal agent is stably dispersed on the surface of the stone to be repaired and renewed, and through the defects such as pores formed on the surface of the stone, efficient repair and renewal of the stone is achieved. Among them, during the preparation process of carbon-based nanoparticles, aluminum dihydrogen phosphate, while acting as a binder, forms an amorphous structure due to the influence of temperature increase, and the amorphous structure has a crack and mosaic state, so that the amorphous structure is combined through bridging hydrogen bonds, so that the hydrogen bonds can maintain an effective combination state with the penetrant, water solvent, nano-silicon oil, sulfoaluminate cement and nano-silicon carbide powder, and thus the stone repair and renewal agent can achieve the purpose of significantly reducing the difficulty and cost of stone surface repair; and because aluminum dihydrogen phosphate decomposes during the heating process to produce partial aluminum metaphosphate, the surface chemical stability and structural strength of the stone to be repaired and renewed are improved through aluminum metaphosphate.

[0083] The "first", "second", "third", "fourth", etc. (if any) referred to in this application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods or devices.

[0084] It should be noted that the descriptions involving "first", "second", etc. in this application are only for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in this field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by this application.

[0085] Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A stone repair and renewal agent, characterized in that: The composition comprises the following components by weight: Sulphoaluminate cement 15-25 parts; 8-11 parts of nano silicon carbide powder; 7-12 parts of nano silicone oil; 2-4 parts of carbon-based nanoparticles; Penetrant 0.4-1.8 parts; 8-12 parts of water solvent; Wherein, the carbon-based nanoparticles are composed of a carbon-based core and a shell covering the carbon-based core; The particle size of the nano silicon carbide powder is 30-100 nm; the preparation method of the carbon-based nanoparticles comprises s1, introducing the carbon-based material into a grinding jar for grinding to obtain a nano-scale carbon-based material; s2, adding aluminum dihydrogen phosphate in a weight ratio of 1:0.2-0.6 to the nano-scale carbon-based material into the grinding jar, and stirring and mixing to obtain a carbon-based material with aluminum dihydrogen phosphate adhered to the surface; s3, adding silicon dioxide in a weight ratio of 1:0.05-0.12 to the carbon-based material with aluminum dihydrogen phosphate adhered to the surface, and Continue stirring to obtain a mixed slurry; s4, introduce the mixed slurry into a vacuum drying oven for drying, and obtain a carbon-based core coating material; s5, grind, ultrasonically disperse and stir, dry and sinter the carbon-based core coating material to obtain carbon-based nanoparticles; and in s3, it also includes adding lithium sulfate in a weight ratio of 1:0.08-0.24 to the nano-scale carbon-based material to the carbon-based material with aluminum dihydrogen phosphate adhered to the surface; the carbon-based core is graphene, graphene oxide and / or silicon carbide fiber; the shell is composed of aluminum dihydrogen phosphate, silicon dioxide and lithium sulfate.

2. The stone repair and renewal agent according to claim 1, characterized in that: In s1, the grinding medium of the grinding jar is ethanol or water, and the grinding speed is 1200-1800 r / min, the time is 4-24 h, and the particle size of the nano-scale carbon-based material is 80-300 nm.

3. The stone repair and renewal agent according to claim 1, characterized in that: In s3, stirring is continued for 2-18 h.

4. The stone repair and renewal agent according to claim 1, characterized in that: In s4, the drying temperature of the vacuum drying oven is 120-280°C, and the drying time is 4-32h.

5. The stone repair and renewal agent according to claim 1, characterized in that: In s5, the grinding is carried out in a grinding jar and anhydrous ethanol is used as a solvent, the ultrasonic dispersion and stirring are controlled for 1-12 hours, the drying is controlled at 100-300°C for 2-24 hours, and the sintering is controlled at 200-400°C for 4-24 hours.

6. The stone repair and renewal agent according to claim 1, characterized in that: The penetrant is diisooctyl maleate sulfonate.

Citation Information

Patent Citations

  • Natural marble crack repairing method

    CN107032711A

  • Graphene antistatic lithium-based sealing curing agent for concrete and preparation method of sealing curing agent

    CN110436880A

  • Repairing agent and method for repairing surface of carbon-based composite material

    CN113248283A

  • Preparation method of core-shell structure, core-shell structure and application

    CN113666379A